PERAN WORD OF MOUTH, KEPERCAYAAN DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI FASHION ONE LOMBOK, NTB - Kevin Sanjaya; Christina Whidya Utami; Gladys Greselda Gosal (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
The purpose of this research is to analyze the effect of word of mouth, trust and store atmosphere on purchase decision at Fashion One Lombok. The research respondents are 103 consumers of Fashion One, Lombok, NTB who are taken by purposive sampling method. The analysis that is used is multiple regression analysis. The independent variables are word of mouth, trust and store atmosphere, while the dependent variable is purchase decision. The result of F hypothesis test indicates that the regression model that is used in the research is stated feasible. The results of the t test analysis show that the variables word of mouth, trust and store atmosphere partially affect positive significant on consumers’ purchase decision of Fashion One Lombok, NTB. Therefore, it can be concluded that if each word of mouth, trust and store atmosphere gets better, it will be able to increase consumers’ purchase decision.